PENGARUH KUALITAS LAYANAN SERTA NILAI YANG DIRASAKAN TERHADAP KEPUASAN PENGGUNA JASA DENGAN CITRA PENJUALAN LELANG DI KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG JEMBER - Yudhiharso, Wiji; Yulisetiarini, Diah; Irawan, Bambang (BISMA: Jurnal Bisnis dan Manajemen, 2015)
Abstract: This study aims to analyze the effects of: (1) service quality and perceived values on customers satisfaction; (2) service quality and perceived values on the image of auction sales; and (3) customers satisfaction on the image of auction sales in the State Assets and Auction Service Office (KPKNL) Jember. This research uses SEM and Analysis Modelling Structure. The population of this study is all customers of KPKNL Jember with the sample consists of 150 respondents. Results show that: (1) service quality and perceived values have significant effect on customers satisfaction;(2) service quality and perceived values have significant effect on the image of auction sale;, and (3) customers satisfaction has significant effect on the image of auction sales in KPKNL Jember. Keywords: Service Quality, Perceived Values, Customer Satisfaction, and Product Image.